Uji Efek Pemberian Ekstrak Temulawak (Curcuma Xanthorrhiza Roxb.) Terhadap Gambaran Histopatologi Ginjal Tikus Putih Jantan Galur Wistar Yang Diinduksi Parasetamol - Klarissa, Chika, dr. Nurhayani, M.Sc, dr. Rochmadina Suci Bestari, M.Sc (2016)
Background: Temulawak (Curcuma xanthorrhiza Roxb.) has antioxidant as a protection of free radicals and reducing NAPQI (N-acetyl-para-benzoquinoneimine) which produced by paracetamol metabolism. Purpose: The objective are to know the influence of temulawak extract to the renal cell of rat which is induced by paracetamol and the increase of temulawak extract dose can also increase renal repair effect to the renal cell damaging of rat which is induced by paracetamol. Methods: This was experimental research with post test only control design. Sample in this research were 28 male rats wistar strain and divided into 4 groups, there are negative control group, first dose group (400 mg/kgBW), second dose group (800 mg/kgBW), and third dose group (1600 mg/kgBW). All groups adapted for 6 days and induced by paracetamol with dose 1350 mg/kgBW on 7th day for 7 days. At the 〖14〗^th day the first, second, and third dose groups will be given temulawak extract for 7 days in a row. On day 〖21〗^st, we made preparate from the rat's renal that painted by Hematoxillin Eosin (HE). Renal histopathological is observed and scored base on quantifying of cell damaging on pyknosis, karyorrhexis, and karyolysis. Data are analized by One Way ANOVA test and Post Hoc Multiple Comparisons (LSD). Result: Result of One Way ANOVA test show that there was difference between 4 groups sample. Result of LSD test show there was a significant of degree between control-second dose group, control-third dose group, second dose-control group, and third dose-control group. Conclusion: Temulawak extract was able to decrease the renal damaging cell and the increase of extract dose can also increase of renal repair effect to the renal cell damaging of rats which is induced by paracetamol. Temulawak extract at dose 1600 mg/kgBW had the effect of renal repair better.